2016
DOI: 10.1016/j.celrep.2016.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mutations Form at CTCF-Cohesin Binding Sites in Melanoma Due to Uneven Nucleotide Excision Repair across the Motif

Abstract: CTCF binding sites are frequently mutated in cancer, but how these mutations accumulate and whether they broadly perturb CTCF binding are not well understood. Here, we report that skin cancers exhibit a highly specific asymmetric mutation pattern within CTCF motifs attributable to ultraviolet irradiation and differential nucleotide excision repair (NER). CTCF binding site mutations form independently of replication timing and are enriched at sites of CTCF/cohesin complex binding, suggesting a role for cohesin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
83
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 28 publications
11
83
1
Order By: Relevance
“…Strikingly, dypirimidine positions 10 and 11 comprised the vast majority of all mutations, whereas mutation density was comparably low at other dipyrimidine or cytosine positions (Figure 3c, 3d). This is consistent with findings by Poulos et al (2016), who suggest that differential rates of repair at specific motif positions cause this asymmetry.…”
Section: Uv-induced Mutations At Insulator Sitessupporting
confidence: 92%
See 3 more Smart Citations
“…Strikingly, dypirimidine positions 10 and 11 comprised the vast majority of all mutations, whereas mutation density was comparably low at other dipyrimidine or cytosine positions (Figure 3c, 3d). This is consistent with findings by Poulos et al (2016), who suggest that differential rates of repair at specific motif positions cause this asymmetry.…”
Section: Uv-induced Mutations At Insulator Sitessupporting
confidence: 92%
“…However, an adequate determination of differential expression would require much larger cohorts (including UV-affected normal skin) and gene panels. Poulos et al ( 2016) reported similar issues even when using RNA-Seq in 36 melanoma samples. Nevertheless, they were able to show that expression of cancerassociated genes in affected TAD loops was statistically different from wildtype TAD loops.…”
Section: Uv-induced Mutations At Insulator Sitesmentioning
confidence: 86%
See 2 more Smart Citations
“…2a.14-21), which are all part of the cohesin complex 32 . Recently, an elevated SNV rate at binding sites of the cohesin complex have been reported for several cancer types by others 33,34 . The cohesin complex is a key player in formation and maintenance of topological chromatin domains 35,36 , suggesting that noncoding mutations could play a role shaping the chromatin structure during cancer development.…”
mentioning
confidence: 95%